Waqf in the Perspective of Mawḍū'i Hadith: Analysis of Hadith Criticism Concerning the Prohibition of Selling Waqf Property - Akrama Hatta; Azwar Azwar (Budapest International Research and Critics University, 2022)
This study aims to determine the quality of the hadith related to the prohibition of selling waqf property and the opinions of the Islamic scholars regarding this matter. This research is a descriptive-qualitative study using the mauḍū'i hadith method with classical and contemporary approach and techniques of hadith criticism. The results of the study show that: (1) The quality of the hadith which is the object of naqd al-ḥadīṡ in this study is assessed as valid, both from the side of the chain (sanad) and the point of view (matan), because it has fulfilled the elements of hadith validity; (2) Regarding the law on the transfer of the function of waqf property, there are differences of opinion among the scholars. Shafi'i is of the opinion that waqf assets cannot be exchanged forever. According to Abu Hanifah, waqf property can be exchanged if the waqf property cannot be managed according to its purpose or because of public benefit and worship. Meanwhile, Ahmad bin Hambal considers that the prohibition on selling waqf property is only for waqf assets that can still be used for a need. As for waqf property that is old or almost unusable, it may be sold and the money bought for a replacement. Meanwhile, exchanging waqf assets for waqf is also permissible, apart from mosque waqf.